2013
DOI: 10.1158/1535-7163.mct-12-1151
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Bortezomib Resistance Identifies Secondary Therapies in a Mouse Myeloma Model

Abstract: Multiple myeloma is a hematologic malignancy characterized by the proliferation of neoplastic plasma cells in the bone marrow. Although the first-to-market proteasome inhibitor bortezomib (Velcade) has been successfully used to treat patients with myeloma, drug resistance remains an emerging problem. In this study, we identify signatures of bortezomib sensitivity and resistance by gene expression profiling (GEP) using pairs of bortezomib-sensitive (BzS) and bortezomib-resistant (BzR) cell lines created from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 46 publications
3
66
0
1
Order By: Relevance
“…Notably, ATRA consistently reduced levels of both NRF2 and POMP in bortezomib-naive and -resistant cells either alone or in combination with bortezomib. Our finding of increased activation of NRF2 is consistent with the data of Stessman et al (45), who found in mouse and human cell line models of myeloma that bortezomib resistance produced a gene signature enriched for downstream targets of this transcription factor, although they did not look at what downstream NRF2 effectors could be involved.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, ATRA consistently reduced levels of both NRF2 and POMP in bortezomib-naive and -resistant cells either alone or in combination with bortezomib. Our finding of increased activation of NRF2 is consistent with the data of Stessman et al (45), who found in mouse and human cell line models of myeloma that bortezomib resistance produced a gene signature enriched for downstream targets of this transcription factor, although they did not look at what downstream NRF2 effectors could be involved.…”
Section: Discussionsupporting
confidence: 92%
“…The second-generation proteasome inhibitors carfilzomib (CFZ) (2), ixazomib (3), and marizomib (4) also are showing improved pharmacological properties and promising responses. Nonetheless, MM cells develop resistance to BTZ, leading to relapse of disease in most patients (5,6).…”
mentioning
confidence: 99%
“…While several prior studies have demonstrated synergism between proteasome and HDAC inhibitors, [35][36][37][38][39][40] the utility of such combinations in models of acquired resistance to proteasome inhibitors is largely unknown. We also demonstrated the generality of this approach for achieving synergism, as different combinations of carfilzomib or oprozomib with vorinostat or entinostat were all effective.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that proteasome inhibitors and HDAC inhibitors synergize to overcome intrinsic resistance, [35][36][37][38][39] though considerably less is known about this potential synergy in models of acquired resistance to proteasome inhibitors. 40 Synergy between bortezomib and STAT3 inhibitors has also been reported. 41 Bortezomib, as well as carfilzomib and oprozomib, also induce expression of antiapoptotic Mcl-1, and the activities of these agents can be enhanced by suppression of Mcl-1 expression or inhibition of Mcl-1 using obatoclax (GX15-070).…”
Section: Introductionmentioning
confidence: 97%